(untitled) (Journal of the College of Basic Education, 2025)
Art is a message that humans use to express their feelings and emotions. It is a sustainable process that deals with the spiritual and human dimension. Therefore, (school theater) is one of the most important educational and pedagogical means that has a role in directly influencing the awareness and culture of the recipient (young people), and contributes to the process of instilling values ​​and principles and developing mental, psychological, emotional, social and aesthetic aspects, in addition to fun and entertainment. The research is divided into four chapters: The first chapter includes the methodological framework of the research, the research problem centered on the following question: (What are the potentials of school theater in educating young people about the dangers of drug abuse)? The research objectives, its importance, and the research serves workers, researchers, those interested and specialists in theater. The chapter concluded with defining the terms, while the second chapter dealt with (the theoretical framework) and included two topics, the first concerned: (the role of theater in combating drugs and its psychological and social effects), while the second topic concerned: (school theater and its role in education, teaching and entertainment) devoted to the research procedures, as it was determined by the intentional method in choosing the sample that was analyzed according to the descriptive analytical method, and the fourth chapter contained the results that the researcher reached, including (the youth represent the important segment in building any society, as it is the responsibility of society and its institutions to provide the best services, means and care to advance them). The research concluded with a set of recommendations and suggestions, a list of sources and references, and appendices, in addition to translating the summary into English